Phosphorus and nitrogen regulate arbuscular mycorrhizal symbiosis in Petunia hybrida. - Eva Nouri; Florence Breuillin-Sessoms; Urs Feller; Didier Reinhardt (PLoS ONE, 2014)
Phosphorus and nitrogen are essential nutrient elements that are needed by plants in large amounts. The arbuscular mycorrhizal symbiosis between plants and soil fungi improves phosphorus and nitrogen acquisition under limiting conditions. On the other hand, these nutrients influence root colonization by mycorrhizal fungi and symbiotic functioning. This represents a feedback mechanism that allows plants to control the fungal symbiont depending on nutrient requirements and supply. Elevated phosphorus supply has previously been shown to exert strong inhibition of arbuscular mycorrhizal development. Here, we address to what extent inhibition by phosphorus is influenced by other nutritional pathways in the interaction between Petunia hybrida and R. irregularis. We show that phosphorus and nitrogen are the major nutritional determinants of the interaction. Interestingly, the symbiosis-promoting effect of nitrogen starvation dominantly overruled the suppressive effect of high phosphorus nutrition onto arbuscular mycorrhiza, suggesting that plants promote the symbiosis as long as they are limited by one of the two major nutrients. Our results also show that in a given pair of symbiotic partners (Petunia hybrida and R. irregularis), the entire range from mutually symbiotic to parasitic can be observed depending on the nutritional conditions. Taken together, these results reveal complex nutritional feedback mechanisms in the control of root colonization by arbuscular mycorrhizal fungi.